KAYROTYPE OF SOL (C HANNA MARULIUS) FRO M INDUS RIVER, PAKISTAN - M. Z. Bhatti; M. Rafiq; A. Mian (Journal of Animal and Plant Sciences, 2013)
Sol (Channa marulius, family: Channidae, order: Perciformes) is an important fish species indigenous to Indo-Pakistan sub-continent, and has a commercial value, adapted to survive in low dissolved oxygen. Three populations (Indus, Indian and Thailand) appear isolated and significant difference between Indus and Indian population has appeared in mansural characters. Karyological studies on Channa marulius suggest a diploid number of 44 for the species but the Indian population and Thailand population are different in number of metacentric and telocentric chromosomes. Sol samples (n =7, 15-20 cm) were collected from Head Tounsa (river Indus) and their gill tissues were removed, torn apart and left in hypotonic solution, fixed and spread over a glass slide, stained with aceto-orcein and studied under microscope (100 X). Study of 45 well spread metaphase suggested a diploid number of 44, 8 metacentric having arm ratio of around 2 and 36 telocentric. Present population shares 2n number of 44 with the stocks of the species present in India and Thailand, yet is different from two other stocks in respect of chromosome morphology (Indian: 40 metacentric + 4 telocentric; Thailand: 4 metacentric + 4 submetacentric + 36 telocentric), suggesting intraspecific differences probably caused by isolation.
Keywords: Channa marulius; Karyological studies; Diploid number; Chromosome morphology; Metacentric; Telocentric; Intraspecific differences; Population isolation; Indus River; Aceto-orcein; Metaphase; Head Tounsa; Submetacentric; Perciformes